The Causal Impact of Solid Fuel Use on Mortality – A Cross- Country Panel Analysis - Irfan, Muhammad; Cameron, Michael P.; Hassan, Gazi (International Journal of Energy Economics and Policy, 2023)
Biomass consumption causes indoor air pollution which impairs health and environment. In this paper, we examine the causal relationship between biomass fuel consumption and measures of life expectancy and infant and child mortality. Using 13 years of cross-country panel data which covers 105 countries over the period 2000-2012, we applied fixed effect model and instrumental variable regression. We find that solid fuel combustion causes increase in infant and child mortality and decreases in male and female life expectancy. A back-of-the envelope calculation suggests that, if the solid fuel consumption gap between low-income and lower-middle income countries were reduced by 50 percent, infant and child mortality in the low-income countries decrease by 16.5 and 29.8 per thousand respectively, and life expectancy would increase by 1.0 and 1.5 years for males and females respectively. Our findings suggest that governments, particularly of developing countries, should focus efforts to reduce solid fuel use.